SCIENCE PROCESS SKILLS ANALYSIS OF CLASS VII STUDENTS ON THE MATTER OF TEMPERATURE, HEAT AND EXPANSION - Hendriyani, Riri; Lestari, Tuti (Department of Science Education, 2024)
The research was conducted to determine the percentage of students' mastery of science process skills at SMPN 30 Padang. The type of research used is mixed methods, which combines quantitative and qualitative research. The data collection technique was carried out by means of a written test of 20 multiple choice questions and conducting interviews as supporting data. The results obtained are in the form of percentage mastery of science process skills per indicator. Then grouped based on 5 categories, namely very less, less, enough, good, very good. Percentage of science process skills obtained by observation/observing 42%; classification/grouping 37%; interpretation 45.5%; predicting 29%; asking questions 24%; hypothesized 37%; planning an experiment 34.5%; using tools and materials 60%; apply concept 19% and communicate 50%.